2011
DOI: 10.1111/j.1529-8817.2011.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYCOBILIPROTEIN COMPONENTS AND CHARACTERISTICS OF THE PHYCOBILISOME FROM A THERMOPHILIC CYANOBACTERIUM MYXOSARCINA CONCINNA1

Abstract: A phycocyanin (PC) and three allophycocyanin (AP) components (designated PC, AP1, AP2, and AP3) were prepared from Myxosarcina concinna Printz phycobilisomes by the native gradient PAGE performed in a neutral buffer system combined with the ion exchange column chromatography on DEAE-DE52 cellulose. PC contained one β subunit () and two α ones ( and ), and it carried two rod linkers ( and ) and one rod-core linker (). AP1 and AP3 were characterized as peripheral core APs, whereas AP2 was an inner-core one. AP2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Among the phycobiliprotein-containing algae, eukaryotic red algae occupy a critical position in the evolution of oxygen-evolving photosynthetic organisms, for they are an inheritor of prokaryotic cyanobacteria and a predecessor of eukaryotic cryptophytes [ 11 , 12 ]. Although PBSs were firstly found from a red microalga Porphyridium cruentum and investigated, the detail understanding of the PBS has been accomplished mostly from the researches on cyanobacterium PBSs [ 6 , 7 , 13 , 14 ]. Nonetheless, the feature that red algae is able to grow within and under intertidal zone makes it necessary to reinforce the investigations on red alga PBSs even if the characteristics of red alga PBSs are believed to be similar to those of cyanobacterium ones [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the phycobiliprotein-containing algae, eukaryotic red algae occupy a critical position in the evolution of oxygen-evolving photosynthetic organisms, for they are an inheritor of prokaryotic cyanobacteria and a predecessor of eukaryotic cryptophytes [ 11 , 12 ]. Although PBSs were firstly found from a red microalga Porphyridium cruentum and investigated, the detail understanding of the PBS has been accomplished mostly from the researches on cyanobacterium PBSs [ 6 , 7 , 13 , 14 ]. Nonetheless, the feature that red algae is able to grow within and under intertidal zone makes it necessary to reinforce the investigations on red alga PBSs even if the characteristics of red alga PBSs are believed to be similar to those of cyanobacterium ones [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the PC and AP proteins dissociated or denatured to a certain extent in the PAGE with a resolving gel in pH≥8.6 [24] . Instead of the Tris−Boric acid buffer, the PCs and APs of Myxosarcina concinna were acceptably prepared by employing the native PAGE performed in Tris−Barbital buffer systems in pH 7.5 [24] [25] . Additionally the R-PE from Palmaria palmata could be prepared by the preparative PAGE with Tris−Gly buffer system in pH 8.8 [26] , and similarly the PAGE performed in the Tris−Gly buffer system was used to analyze a R-PE component of the phycobilisomes from Polysiphonia urceolata [27] .…”
Section: Introductionmentioning
confidence: 99%